Characteristics of fresh and frozen semen of Red Chittagong Cattle (Bangladesh Journal of Animal Science, 2022)
Semen production from breeding bulls used in Artificial Insemination (AI) program is of great importance in cattle breeding. Good quality semen has positive effect on the fertility of cows and heifers. The aim of this study was to evaluate the quality and assessed as the freezing ability of Red Chittagong Cattle (RCC) bull with fresh-diluted semen and frozen semen. The parameters of semen characteristics included were volume per ejaculate (ml), percentage of mass motility, normal and abnormal sperm, and sperm concentration (million/ml). The highest mass motility was found in bull ID No. 4 and the lowest in bull ID No. 1 but the highest sperm concentration was found in bull ID No. 3 with lowest in bull ID No. 2 in fresh semen. Highly significant (p